THE INFLUENCE OF E-WOM ON PURCHASE DECISION, MEDIATED BY CUSTOMER TRUST AND PERCEIVED VALUE, AMONG MARKETPLACE USERS IN INDONESIA - Aya Celestia; Hotlan Siagian; Roy Setiawan (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2026)
This study aims to examine the influence of E-WOM on purchase decisions through the mediating role of customer trust and perceived value. This study was performed among Indonesian marketplace users. This research uses a quantitative approach, with survey data collected from 202 Generation Z individuals. Data were collected using a five-point Likert-scale questionnaire distributed via social media platforms WhatsApp, Instagram, and Facebook. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that E-WOM affects customer trust, perceived value, and purchase decisions. Customer trust influences purchase decisions and partially mediates the effect of E-WOM on them. In contrast, perceived value does not affect purchase decisions and does not mediate the relation of E_WOM on purchase decision. These findings suggest that customer trust plays a more critical role than perceived value in driving purchase decisions for Generation Z consumers. The study contributes to the digital consumer behavior literature by reinforcing the applicability of the S–O–R framework and highlighting the dominant mediating role of trust. Practically, the results imply that marketplace platforms and sellers should prioritize strategies that enhance credible E-WOM and strengthen consumer trust rather than relying solely on value-based or price-driven approaches.